Analysis of the Factors Affecting the Absorption of the Special Allocation Funds for the Representatives - Balqiah Dengagi; Haris Maupa; Sumardi Lasise (Hasanuddin Journal of Business Strategy, 2021)
The study is aimed to examine budget planning associated with budget absorption, quality of human resources, budget execution, and administration in the National Population and Family Planning Board (BKKBN) in South Sulawesi Province. The study used primary data collected from the questionnaire The respondent was directed to answer the questionnaire posted online using Google form. The sampling technique used is a saturated sample in which the entire population of the study is taken, which are three respondents from DAK KB managers in 24 districts/cities. The data analysis technique used in this study is multiple linear regression analysis. The results showed that budget absorption, quality of HR, and administration had a significant positive direct effect on budget planning. Differently, budget execution had a direct positive and insignificant effect on budget planning. This indicates that in implementing its budget, the DAK KB sub-sector managers tend to ignore the rules and plans that have been set in the implementation of their budget.